123 ROLE OF NUCLEAR FACTOR-kB IN THE PROCESS OF LUNG TRANSPLANT REJECTION. (1st January 2006) - Joodi, R.; LaVoy, J.; Xu, J.; Mora, A. L.; Brigham, K. L.; Rojas, M.
Abstract : Over the last 20 years, lung transplantation has evolved into a viable treatment option for a variety of end-stage pulmonary diseases. Long-term survival following lung transplantation remains low because chronic rejection complicates up to 60% of transplanted lungs. Chronic rejection is manifested by a specific scarring process of the bronchial tubes called obliterative bronchiolitis (OB), which is generally untreatable. We work under the general hypothesis that chronic rejection results from the activation of several cellular components of the immune system that promote the development of OB. We propose to use a permeable protein, GST-IkBa-(DN)-MTS, which has the ability to inhibit NF-kB activity. The NF-kB signal transduction pathway can regulate immune responses activated against foreign antigens present in transplanted tissues. Using a mouse model that consists of an allogenic tracheal transplant, we aim to study the effect of the systemic administration of IkBa-(DN) in the development of OB. Our data show a decrease in the fibrosis in the animals treated with the permeable inhibitor. The reduction in OB was associated with a decrease in the levels of the profibrotic factor TGFb1 in the transplanted trachea. The potential implications of this work are relevant to the clinical field by determining essential mechanisms responsible for chronic rejection in the lung and the potential development of novel therapies.